Sulfur and carbon isotopes in scapolite-bearing granulites of the São José do Rio Pardo area, Brazil - Iyer, S. S.; de Oliveira, M. A F [UNESP]; Hoefs, J.; Krouse, H. R. (Elsevier, 1992)
Sulfur and carbon isotope compositions of ten scapolites from granulite-facies rocks of the São José do Rio Pardo area, Guaxupé Complex, Brazil, were measured. Scapolite is the primary and major rock-forming mineral in these rocks (up to 40 volume %). The isotopic composition of the sulfate and carbonate group in the scapolite structure has δ34S values of +1.0‰ to +6.7‰, and δ13C values of -14.3‰ to -6.3‰, respectively. The sulfur isotope data may be related to an upper mantle (external) or lower crustal (internal) source for the sulfur, whereas the carbon appears to have been derived from an internal source. Thus, the carbon and sulfur isotope data can be explained without invoking an external (mantle) source. © 1993.
Keywords: carbon; granulite; isotopic composition; scapolite; sulphur; Brazil, Sao Jose do Rio Pardo